Crosstalk between dendritic cells and regulatory T cells: Protective effect and therapeutic potential in multiple sclerosis - Li, Ruoyu; Li, Hui; Yang, Xiaoyan; Hu, Huiru; Liu, Peidong; Liu, Hongbo (Frontiers in Immunology, 2022)
Multiple sclerosis (MS) is a chronic inflammatory disease of the central nervous system related to autoimmunity and is characterized by demyelination, neuroinflammation, and neurodegeneration. Cell therapies mediated by dendritic cells (DCs) and regulatory T cells (Tregs) have gradually become accumulating focusing in MS, and the protective crosstalk mechanisms between DCs and Tregs provide the basis for the efficacy of treatment regimens. In MS and its animal model experimental autoimmune encephalomyelitis, DCs communicate with Tregs to form immune synapses and complete a variety of complex interactions to counteract the unbalanced immune tolerance. Through different co-stimulatory/inhibitory molecules, cytokines, and metabolic enzymes, DCs regulate the proliferation, differentiation and function of Tregs. On the other hand, Tregs inhibit the mature state and antigen presentation ability of DCs, ultimately improving immune tolerance. In this review, we summarized the pivotal immune targets in the interaction between DCs and Tregs, and elucidated the protective mechanism of DC-Treg cell crosstalk in MS, finally interpreted the complex cell interplay in the manner of inhibitory feedback loops to explore novel therapeutic directions for MS.